PERKEMBANGAN DELIK ZINA DALAM YURISPRUDENSI HUKUM PIDANA - Putra Rozi, Zulfiqar Bhisma (Veritas et Justitia, 2019)
This article examines the concept of adultery as regulated in Article 284 of the Criminal Code. Behind this penal ruling is the intention to protect the sanctity of marriage contracts. Outside the purview of this article is extra marital sex. The author main argument is that Judges using their authority to extract and formula existing unwritten society’s appraisal and judgment on extra-marital sex. The purpose of which is to make possible penalization of couples considering guilty of committing extra marital sex.  A study of existing laws and regulations, plus relevant court judgments will be undertaken, to explore the possibility of changing and extending the concept of zina (adultery) to encompass also extra-marital sex.